Analysis of the use of Prepositions in English-Uzbek Translations (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article studies the translation and role of prepositions in English and Uzbek. By analyzing the differences between English prepositions and their Uzbek equivalents, ambiguities and complexities in translation are considered. It also discusses the role of prepositions, their grammatical and semantic functions. The article also discusses the aspects that should be paid attention to in the correct selection and placement of prepositions in translation, and gives practical recommendations.